Age Differences by Sex in Antiretroviral‐Naïve Participants: Pooled Analysis from Randomized Clinical Trials. (May 2018) - Tracy, LaRee A.; Struble, Kimberly; Firnhaber, Cynthia; Smeaton, Laura; Lake, Jordan E.; Bell, Tanvir; Soon, Guoxing (Gregg); Yan, Jin; Schnippel, Kathryn; Cohn, Susan E.
Abstract : N/A: Age and sex effects on antiretroviral therapy (ART) response are not well elucidated. Our pooled analysis of 40 randomized clinical trials measured the association of age and sex on CD4+ T cell count changes and virologic suppression using multivariable regression modeling. The average increase in CD4+ T cell count from baseline to week 48 was 17.3 cells/mm 3 lower and clinically insignificant (95% confidence interval −30.8 to −3.8) among women ages ≥ 50 years ( n = 573), compared to women ≤ 35 years ( n = 3, 939). Results were similar for men. Virologic suppression odds were 60% and 21% times greater among participants ≥50 years compared to ≤35 years, in women and men, respectively. In both sexes, larger increases in CD4+ T cell count changes were observed in younger, compared to older, participants; however, virologic suppression was higher in older, compared to younger, participants suggesting a non‐sex‐specific age effect response to ART.